(untitled) (Revista de Estudios Europeos, 2026)
Energy efficiency is a cornerstone of the Green Deal: buildings account for 40% of energy consumption and 36% of CO₂ emissions in the European Union. From Rio 1992 to Paris 2015 —including Kyoto and SDG 7 arising from the New York Summit— the international framework consolidated this priority, which Spain incorporates into its National Integrated Energy and Climate Plan (PNIEC) and Law 7/2021. The Green Deal, Renovation Wave, and Taxonomy drive investment and digitalization. Directives 2010/31, 2012/27, 2018/844, and 2024/1275 establish minimum standards requiring the renovation and digitalization of the building stock, aiming for zero-emission buildings by 2050.